Foreign directors, foreign ownership, and carbon emission disclosure: Evidence from Indonesia environmentally sensitive companies - Diajeng Fitri Wulan (Universitas Pendidikan Nasional, 2022)
Business organizations were increasingly being held accountable for their social and environmental impacts. Disclosure of carbon emissions is an issue that is starting to develop in various countries, including Indonesia, related to climate change's effects on organizations' sustainability. National governments and non-governmental organizations (NGOs) needed to take action to urge companies to reduce carbon emissions, one of which is full disclosure of their carbon emissions. This study aimed to see whether knowing the presence of foreign directors, foreign commissioners, and foreign ownership affects the disclosure of carbon emissions. This study also used three control variables: Company Size, ROA, and DER. The samples of this research were companies listed on the IDX that are sensitive to the environment from 2019 to 2021, which issued a Sustainability Report resulting in a total of 41 companies. The test was carried out by performing multiple regression tests. The results showed that foreign commissioners, company size, and DER significantly influenced the disclosure of carbon emissions. Therefore, managers should consider balancing between foreign and local commissioners to benefit from a rich, heterogeneous resource encompassing the various merits of both types of directors, with particular emphasis on foreign commissioners' international exposure and experience.